Characterization of induced struvite formation from source-separated urine using seawater and brine as magnesium sources - Liu, Bianxia (2016)
Struvite (MgNH4PO4·6H2O) precipitation is widely used for nutrient recovery from source-separated urine in view of limited natural resources. Spontaneous struvite formation depletes the magnesium in hydrolyzed urine so that additional magnesium source is required to produce induced struvite for P-recovery. The present study investigated the morphology and purity of induced struvite crystals obtained from hydrolyzed urine by using seawater and desalination brine as low cost magnesium sources. The results demonstrated that both seawater and brine were effective magnesium sources to recover phosphorus from hydrolyzed urine. Crystals obtained from synthetic and real urine were revealed that the morphology was feather and coffin shape, respectively. Structural characterization of the precipitates confirmed that crystallized struvite was the main product. However, co-precipitates magnesium calcite and calcite were observed when seawater was added into synthetic and real urine, respectively. It was found that the presence of calcium in the magnesium sources could compromise struvite purity. Higher struvite purity could be obtained with higher Mg/Ca ratio in the magnesium source. Comparative analysis indicated that seawater and brine had similar effect on the crystallized struvite purity.